Needs assessment of the advanced Ghana field epidemiology and laboratory training program, April 2024: lessons learned and best practices - Bonkano Laurent Comlan, Mariame; Frimpong, Joseph Asamoah; Noora, Charles Lwanga; Ameme, Donne Kofi; Usman, Aishat Bukola; Lokossou, Virgil Kuassi; Thomas, Peter Evans; Barradas, Danielle Thompson; Kazambu, Ditu; Kazoora, Herbert Brian; Kenu, Ernest; Antara, Simon Nyovura; et al. (Frontiers in Epidemiology, 2025)
BackgroundThe Ghana Field Epidemiology and Laboratory Training Program (GFELTP) trains skilled field epidemiologists to strengthen surveillance systems and respond to public health threats. This assessment aimed to evaluate GFELTP's achievements, identify gaps in training and service delivery, and provide recommendations for improvement.MethodsA convergent mixed-methods evaluation was used, combining a self-administered questionnaire, program record reviews (graduation rates, surveillance outputs, publications), and three Focus Group Discussions (FGDs) involving staff, alumni, mentors, and residents. Thematic content analysis and triangulation with quantitative data were conducted to assess achievements and training gaps from 2007 to 2024.ResultsTwenty-four participants (4 staff, 5 alumni, 5 mentors, and 10 residents) were interviewed. GFELTP operates as a regional program, training individuals from seven African countries. From October 2007 to March 2024, it enrolled 17 cohorts, producing 192 graduates and training 35 current residents. Of the graduates, 72% (139/192) were Ghanaians. Most graduates (89%) came from the human health sector, with 8% from the animal health sector and 3% from environmental health. Residents and graduates conducted over 200 outbreak investigations and evaluated more than 300 surveillance systems. They also delivered over 350 scientific presentations locally and internationally. FGDs revealed several challenges: limited mentorship funding, low program visibility, inadequate digital capacity for modern public health practices, and limited funding for resident exchange programs.ConclusionsGFELTP has made substantial contributions to public health capacity-building in Ghana and West Africa, through training, outbreak response, and scientific engagement. Key strengths include its regional reach, robust alumni network, One Health integration, and strategic collaborations. However, challenges remain in mentorship support, online visibility, and funding for resident development opportunities. Addressing these gaps through sustained mentorship, improved stakeholder engagement, and enhanced resource mobilization will further strengthen the program's impact and long-term sustainability in building a resilient public health workforce.